Composted Municipal Green Waste Enhances Tree Success in Opencast Coal Land Reclamation in Wales. Issue 12 (September 2019) - Haigh, Martin; Desai, Mansi; Cullis, Mike; D'Aucourt, Margaret; Sansom, Ben; Wilding, Gill; Alun, Elanor; Garate, Sergio; Hatton, Liz; Kilmartin, Marianne; Panhuis, Wilhemina; Jenkins, Rhian
The United Kingdom has a problem in the disposal of municipal green waste (MGW). This is unsuitable for landfill, but when properly composted may be beneficial to tree growth. A formal controlled trial of the 11-year growth (height, diameter at breast height [DBH]) and survival of 3 tree species was evaluated on degraded former opencast coal land on the margins of UNESCO's Blaenavon Industrial Landscape World Heritage site in South East Wales. Forest reclamation is considered a viable cost-effective approach to reclamation but success may be compromised by infertile and seriously compacted substrates, the depleted bio-geoecological system, and a lack of funding. In this trial, trees were (or were not) supplied, on planting, with 0.75 kg per stem of composted MGW – here a mixture of 40% domestic food waste and 60% garden waste. Results show that the application of MGW made no significant difference to either tree height or DBH. Survival rates were highest for Common Alder ( Alnus glutinosa (L.) Gaertn.) followed by Silver Birch ( Betula pendula, Roth) and European Larch ( Larix decidua Mill.). However, Silver Birch and Larch treated with MGW compost had significantly greater survival rates, whereas Alder had significantly lower survival rates, compared with trees planted without MGW treatment.